Adsorptive Removal of Cd(II) Ions using Core-Shell Polystyrene@NiFeAl-LDH Nanocomposite: Optimization, Isotherm, and Kinetics Study - Shahad A. Raheem; Ahmed A. Mohammed (Bulletin of Chemical Reaction Engineering & Catalysis, 2026)
In this study, a core-shell nanocomposite was successfully prepared using NiAlFe-LDH as a core coated with polystyrene (PS) nanoparticles with an LDH:PS ratio of 3:1 (PS @NiAlFe-LDH) for the removal of cadmium (Cd2+) from aqueous solutions. PS nanospheres were prepared from styrene monomer recovered from Styrofoam waste. The prepared PS@NiAlFe-LDH was characterized for its structural morphology, elemental composition, surface area, and pore morphology. Results indicated the successful formation of PS nanosphers core coated by platelet LDH shell and a successful adsorption of Cd2+ ions. The maximum adsorption efficiency (95.53%) was achieved under the optimal conditions: pH of 6, PS@NiAlFe-LDH dosage of 0.15 g/100 mL, shaking speed of 200 rpm, and an initial Cd2+ concentration of 100 mg/L at a 90-minute contact time. Langmuir isotherm model was the most accurate in describing the adsorption process with a maximum adsorption capacity of 227.273 mg/g. The pseudo-second-order (PSO) kinetics model described the adsorption behaviour of cadmium ions on PS@NiAlFe-LDH surface as the calculated values from the model were close to the experimental values. The adsorption mechanism was a combination of electrostatic attraction, surface complexation/ion exchange and internal diffusion within the pores. PS@NiAlFe-LDH demonstrated significant reusability, with an efficiency of 57.56% after six regeneration cycles. In conclusion, this study indicates that PS@NiAlFe-LDH nanocomposite exhibits high quality and excellent efficiency in removing cadmium ions from aqueous solutions, owing to its porosity and abundance of active groups on its surface, as well as structural stability after adsorption, which makes it a promising material for environmental remediation applications. Copyright © 2026 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).